2019
DOI: 10.1016/j.clinthera.2018.12.001
|View full text |Cite
|
Sign up to set email alerts
|

A Phase I, Randomized, Crossover, Open-label Study of the Pharmacokinetics of Solriamfetol (JZP-110) in Healthy Adult Subjects With and Without Food

Abstract: Purpose: Solriamfetol (JZP-110), a selective dopamine and norepinephrine reuptake inhibitor with robust wake-promoting effects, is currently being evaluated for the reduction of sleepiness and improvement of wakefulness in patients with narcolepsy and obstructive sleep apnea. The purpose of this study was to evaluate the effect of food on the pharmacokinetic (PK) parameters and bioavailability of solriamfetol at the highest intended therapeutic dose in healthy adults and to characterize its renal excretion und… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
21
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 21 publications
(23 citation statements)
references
References 22 publications
2
21
0
Order By: Relevance
“…Solriamfetol exhibits linear PKs over a dose range of 42-1008 mg (Table 2) [26]. It is rapidly absorbed after oral administration (median t max , 2 h); administration with food delays absorption by ~ 1 h but does not affect overall exposure (minimal changes in C max and AUC ∞ ) [28]. It is not extensively protein bound (13-19%) and has a mean t ½ of ~ 7 h [26].…”
Section: Pk/ddi Potentialmentioning
confidence: 99%
“…Solriamfetol exhibits linear PKs over a dose range of 42-1008 mg (Table 2) [26]. It is rapidly absorbed after oral administration (median t max , 2 h); administration with food delays absorption by ~ 1 h but does not affect overall exposure (minimal changes in C max and AUC ∞ ) [28]. It is not extensively protein bound (13-19%) and has a mean t ½ of ~ 7 h [26].…”
Section: Pk/ddi Potentialmentioning
confidence: 99%
“…7 The major route of solriamfetol elimination is via urinary excretion, with approximately 90% of drug excreted unchanged within 48 hours, and ß1% of the dose excreted as the minor metabolite, N-acetyl solriamfetol. 7 Renal impairment, as well as hemodialysis in individuals with end-stage renal disease (ESRD) could affect the pharmacokinetics (PK) of solriamfetol. Therefore, in accordance with US Food and Drug Administration guidance for PK studies in patients with impaired renal function, 8 this study was designed to evaluate the PK of solriamfetol in participants with renal impairment and those with ESRD undergoing hemodialysis compared with healthy participants with normal renal function.…”
mentioning
confidence: 99%
“…Solriamfetol has high solubility and high permeability and is considered a Biopharmaceutics Classification System class 1 compound. Solriamfetol is rapidly absorbed after oral administration, with median time to maximum plasma concentration (C max ) at 2 hours after dosing and an apparent elimination half‐life (t 1/2 ) of ∼6 hours . Consumption of a high‐fat, high‐calorie meal does not change the rate and extent of solriamfetol exposure but delays time to C max by 1 hour, which likely has minimal clinical significance .…”
mentioning
confidence: 99%
“…3 The PK profile of solriamfetol in this study is consistent with what has previously been reported in healthy adults. 5,6 Solriamfetol was rapidly absorbed, with a median t max of 2 and 3 hours following oral administration of 300-and 900-mg doses, respectively. An approximately 3-fold higher solriamfetol C max and 3.5-fold greater AUC 0-inf were observed following the 900-mg dose compared with the 300-mg dose, indicating dose-proportional PK.…”
Section: Discussionmentioning
confidence: 99%
“…1 Solriamfetol is rapidly absorbed following oral administration, has a terminal half-life of approximately 6 hours, and is mostly excreted in the urine unchanged (>90%). 5 Renal impairment increases overall exposure to solriamfetol, with greater increases in exposure as the level of renal function worsens. 6 The safety and efficacy of solriamfetol (maximum dose evaluated, 300 mg) in reducing EDS in patients with narcolepsy or OSA have been established in phase 3 clinical studies, including 6-and 12-week randomized, double-blind, placebo-controlled studies and a 1-year open-label extension study.…”
mentioning
confidence: 99%